2022
DOI: 10.1002/ange.202210640
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Light‐Dependent Spatial Distribution of Spin Defects in Carbon Nitride

Abstract: Carbon nitride (CN) is a heterogeneous photocatalyst that combines good structural properties and a broad scope. The photocatalytic efficiency of CN is associated with the presence of defective and radical species. An accurate description of defective states—both at a local and extended level—is key to develop a thorough mechanistic understanding of the photophysics of CN. In turn, this will maximise the generation and usage of photogenerated charge carriers and minimise wasteful charge recombination. Here the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…It is widely accepted that triplet states have a long lifetime. 56,57 Thus, we can safely believe that the CT and triplet states together promote the separation and transfer of charge carriers in the aggregates. 58 The above results reveal that the SS-CNP aggregates have efficient separation and transfer of charge carriers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is widely accepted that triplet states have a long lifetime. 56,57 Thus, we can safely believe that the CT and triplet states together promote the separation and transfer of charge carriers in the aggregates. 58 The above results reveal that the SS-CNP aggregates have efficient separation and transfer of charge carriers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results showed that all samples display a Lorentzian signal centrosymmetric at g = 2.0042, attributed to the local unpaired electrons belonging to sp 2 hybridized C atom in the p orbital. 36 The EPR signal, on the one hand, represented the generation of amorphous carbon nitride, 37 while on the other hand, it was used as evidence for the formation of vacancies. 38 The signal values of DCN and TDCN were sequentially enhanced compared to g-C 3 N 4 , which implied that the same type of defects was present in both samples.…”
Section: Physicochemical and Electronic Propertiesmentioning
confidence: 87%
“…For a more in-depth understanding of the measurements conducted with EPR and related techniques, we recommend consulting the following articles. [113,114] Moreover, the re-organization of the heptazine motifs might cause not only the distortion in π-π conjugation but also new appearing polar functional groups. For this purpose, Fourier transform infrared spectroscopy (FTIR) plays a crucial role since different reagents and conditions might lead to distinct defects whether cyano, amino or other types.…”
Section: Unraveling the N-vacancy Puzzle: Synthesis Strategiesmentioning
confidence: 99%
“…Nevertheless, certain pioneering studies employing pulsed dipolar and hyperfine spectroscopies have unveiled the precise positioning of two radical pairs, approximately 2 nm apart (equivalent to roughly four tri‐s‐triazine moieties). For a more in‐depth understanding of the measurements conducted with EPR and related techniques, we recommend consulting the following articles [113,114] …”
Section: Unlocking N‐vacancies In Cn: Characterization Techniquesmentioning
confidence: 99%